2018
DOI: 10.1029/2018sw001919
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Index Derived From All Sky Imagers for Space Weather Impact on GPS

Abstract: Global Positioning System (GPS) signals passing through the auroral ionosphere, which exhibits multiscreen electron density structuring, maybe scintillated causing observation and possibly positioning errors. It is advantageous to determine the magnitude of GPS signal scintillation associated with a given level of auroral brightness observed around the signal's ionospheric pierce point (IPP). Such information would enable the exploitation of auroral image observations in space weather monitoring and help in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Polar cap arcs are also associated with scintillation (Jayachandran et al., 2017; Wang et al., 2021). The scintillation tends to occur on the leading and trailing edges of auroral forms, suggesting that density irregularities develop at density gradients that are created by particle precipitation (Loucks et al., 2017; Mrak et al., 2018; Mushini et al., 2018; Semeter et al., 2017; van der Meeren et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Polar cap arcs are also associated with scintillation (Jayachandran et al., 2017; Wang et al., 2021). The scintillation tends to occur on the leading and trailing edges of auroral forms, suggesting that density irregularities develop at density gradients that are created by particle precipitation (Loucks et al., 2017; Mrak et al., 2018; Mushini et al., 2018; Semeter et al., 2017; van der Meeren et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2017) defined the polar cap hot patch and suggested it may associate with polar cap arcs and stronger scintillations. Furthermore, the positive relations of auroral emissions and phase scintillations have been statistically established, generally higher values of emission intensity correspond to stronger phase scintillation (Kinrade et al, 2013;Mushini et al, 2018). Additionally, Kintner et al (2002) and Jayachandran et al (2009) reported TEC variations due to an auroral arc, but there were no analysis on scintillations.…”
mentioning
confidence: 99%
“…At high latitudes, the effects of scintillations associated with a variety of ionospheric irregularities have been investigated in many studies (e.g., Jayachandran et al, 2017;Jin et al, 2014Jin et al, , 2015Jin et al, , 2016Moen et al, 2013;Mushini et al, 2018;Oksavik et al, 2015;van der Meeren et al, 2014van der Meeren et al, , 2015Wang et al, 2016;and references therein). In this study, we are focusing on the polar cap arc, which is an aurora arc in the polar cap region that is primarily formed during northward interplanetary magnetic field (IMF) and under a quiet geomagnetic condition (e.g., Fear et al, 2014;Kullen, 2012;Xing et al, 2018;Zhu et al, 1997).…”
mentioning
confidence: 99%